P‐154: Retardation Free Polarizer for IPS Display. Issue 1 (30th May 2018) - Min, Kyung Suk; Kim, Jin Ho; Lee, Sang Min; Ko, Tae Woon; Park, Mi Kyung; Kim, Kyoung Hoon; Kim, Hyung Seung; Kim, Jong Dae; Kim, Jeom Jae; Jun, Mike; Kang, In Byeong
Abstract : Retardation‐Free Polarizer, polarizer with no inner protective film, provides various advantages. With its distinct structure, it enables slim design and enhancement in quality assurance for IPS LCD devices. Compared to other LCD modes, IPS mode has better fit for adapting RF Polarizer in off angle black luminance.